MEASURES OF USING CHANTS IN DEVELOPING 5-6-YEAR-OLD CHILDREN’S ENGLISH VOCABULARY - Thi Thanh Huong, Nguyen; Thi Tu Anh, Pham (HNUE Journal of Science: Journal of Educational Science, 2024)
In the current globalization trend, introducing preschool children to English is an important “strategy” to help children form and develop skills in using English as a second language. Rhyming poems with rhyme, rhythm and repetition of words and sentence patterns significantly encourage preschool children to acquire English vocabulary. This effective tool supports language learning through a fun and memorable learning experience. Using document research and analysis, synthesis and comparison, the article points out three measures to use rhyming poems to develop English vocabulary for preschool children aged 5-6, which are: Selecting rhyming poems with vocabulary appropriate to the child’s ability; Composing rhyming poems on familiar topics; Creating interactive situations in the process of organizing activities using rhyming poems to develop English vocabulary for children aged 5-6. By enhancing vocabulary development through engaging rhymes, teachers can create a stimulating learning environment that supports children’s language acquisition and encourages their love of learning English at later stages.